Tratamento da leishmaniose visceral com anfotericina B lipossomal, Minas Gerais, 2008-2012 - Bruna Dias Tourinho (2015)
Background: Visceral leishmaniasis (VL) is a serious, systemic and fatal disease if not diagnosed and treated in time. In recent decades it expanded into the urban environment, showing an increase of mortality rates in Brazil and in Minas Gerais. Liposomal amphotericin B is the less toxic option for VL treatment, indicated to a special group of patients who are at increased risk of death. It is a high cost drug, purchased by the Health Ministry at reduced prices and had its distribution decentralized in Minas Gerais since 2008. It is a high cost drug, purchased by the Health Ministry at reduced prices and had its distribution decentralized in Minas Gerais since 2008. Despite the growing increase in its use, little is known about authorized treatments, the adequacy of indications to the recommended criteria, the clinical and epidemiological characteristics and factors associated with death of patients. Objective: To evaluate the treatment of VL with liposomal amphotericin B in the State of Minas Gerais from 2008 to 2012. Method: (i) descriptive epidemiological study and (ii) historical cohort of patients treated with liposomal amphotericin B. Treatment request and evolution forms, National System for Notifiable Diseases (SINAN) and Mortality Information System (SIM) were used as secondary data. Results: 646 treatment requests were made and 577 patients were treated, enabling 22.4% of patients with VL in the state to use the product. The decentralization of treatment reached patients residing in 97 municipalities of 20 Regional Health Units (URS's) and 29 municipalities of 15 URS's requested treatment. The municipality and the URS of Belo Horizonte had the highest proportions of requests (77.1% and 79.9%) and resident patients (41.5% and 68.0%). About 83.8% of treatment requests meet the criteria use of the drug. Renal failure (58.4%) and age over than 50 years (37.8%) were the most frequent indications. Liposomal amphotericin B was the first choice of treatment in about 45.6% of patients, consisting of males (75.4%), aged 50-64 (25.5%) and 35-49 years (23.2%). The overall lethality rate was 19.4%, higher in 2009 (32.5%). Factors associated with death in patients treated with liposomal amphotericin B were: age over 35 years (OR: 2,64; CI: 1,46-4,78), jaundice (OR: 2,17; CI: 1,25-3,76), kidney disease (OR: 2,83; CI: 1,66-4,85), infections (OR: 2,46; CI: 1,47-4,09), edema (OR: 1,97; CI: 1,15-3,36), platelets <50,000 / mm3 (OR: 3,56; CI: 2,12-5,96), AST> 100 U / L (OR: 2,19; CI: 1,26-3,76) and assistance in non-specialized institutions (OR: 1,86; CI: 1,01-3,44). Conclusion: The process of expansion and decentralization of access to liposomal amphotericin B in Minas Gerais reflects a positive response from the assistance and surveillance teams of regional and municipal levels of the state. Factors associated with death identified in this study may allow early identification of patients prone to this outcome, which will enable the appropriate clinical management of them and contribute to the reduction of VL lethality. The availability of a less toxic treatment is not the only strategy required for the reduction of VL lethality. Efforts to improve care quality and the structuring of activities related to VL surveillance and control continuously will contribute for favorable results.